Energy-Aware Technology-Based DVFS Mechanism for the Android Operating System - Silva-Filho, A. G.; Bezerra, P. T. L.; Silva, F. Q. B.; C. Júnior, A. L. O.; Santos, A. L. M.; Costa, P. H. R.; Miranda, R. C. G. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
DVFS is an efficient energy saving technique for processors during program execution time. In this paper, we will focus efforts on 3G and Wi-Fi technologies to evaluate the impact of energy consumption when combined with DVFS mechanism based on the Android operating system. An experimental infrastructure with basis on Samsung's Smartphone was used to evaluate the proposed strategy to reduce energy consumption. Results of the proposed approach was compared with nonoptimized approach and an average reduction about 30% in terms of energy consumption was obtained when compared with performance mode.